Sunan Giri's Da'wah Network and Islamization in Sulawesi and Nusa Tenggara - Hilful Fudhul; Ahmad Muhajir; Siska Nurazizah Lestari (JUSPI (Jurnal Sejarah Peradaban Islam), 2021)
This article explores the da'wah network of Sunan Giri and other ulamas in Eastern Indonesia, such as in Gowa, Lombok, Maluku, Bima to Manggarai. This da’wah network refers to the relationship between Giri and Datuk ri Bandang, both teacher and student. This research uses the historical method. The primary sources used include the manuscripts of Bo Sangaji Kai, Panambo Lombok, Lontara Gowa, and Lontara Wajo. The results of the study concluded that Islamization in the archipelago is in one da’wah network. Ulama spread across the archipelago has a scientific chain from an extensive Wali Songo da’wah network. Sunan Giri and his da’wah network (Datuk ri Bandang) were central in Islamizing the eastern region.